Inflammation in the neonatal period and intrauterine growth restriction aggravate bronchopulmonary dysplasia - Hiroaki Kurata; Masayuki Ochiai; Hirosuke Inoue; Takeshi Kusuda; Junko Fujiyoshi; Masako Ichiyama; Yoshifumi Wakata; Hidetoshi Takada (Pediatrics and Neonatology)
Background: To investigate the hematological features of infants with bronchopulmonary dysplasia (BPD) and their relationships with clinical severity. Methods: This prospective observational study enrolled 73 BPD patients from a total of 331 infants with a birth weight of <1500 g from 2005 to 2013. The clinical severity of BPD was defined by the duration of oxygen supplementation and positive pressure ventilation (PPV) in line with the diagnostic criteria of BPD. The hematological status and cytokine levels were surveyed from blood samples at birth and at 2 and 4 weeks of life. Results: Thirty-four (46.6%) cases were classified as “moderate-to-severe” BPD. Small-for-gestational-age (SGA) was associated with the severity of BPD (OR: 5.05; 95% CI: 1.45 to 17.2). The CRP level at 2 weeks (partial regression coefficient [rc]: 21.8; 4.01 to 39.7) and the neutrophil count at 4 weeks (0.005; 0.001 to 0.007) were positively correlated with the oxygenation period. The PPV period was found to be correlated with the CRP level at 2 weeks (27.2; 14.9 to 39.5), and the neutrophil count (0.003; 0.001 to 0.004) at 4 weeks. Conclusion: The aggravation of BPD was associated with both SGA at birth and inflammation during neonatal period. Key Words: chronic lung disease, etiology, factor, small-for-gestational-age